Hydrogen sulfide regulates autophagy in nucleus pulposus cells under hypoxia. Issue 4 (8th December 2021) - Yue, Lei; Hu, Yongkai; Fu, Haoyong; Qi, Longtao; Sun, Haolin
Abstract: Objective: Hydrogen sulfide (H2 S) has been found to act as an important gasotransmitter to regulate cell activities. This study aimed to investigate the effect of H2 S on autophagy of nucleus pulposus (NP) cells under hypoxia and possible mechanism. Materials and Methods: NP cells were isolated from rat caudal discs. Cobalt chloride was used to mimic hypoxia, sodium hydrosulfide was used to emulate exogenous H2 S and 3‐methyladenine was used to block cell autophagy. Cell viability was assessed by phase contrast microscope and Cell Counting Kit‐8 method. Moreover, expression of key autophagic proteins was analyzed via western blotting, and transmission electron microscopy was performed to detect autophagosomes. Results: Hypoxia markedly impaired NP cell proliferation compared with control. Whereas H2 S provided pro‐proliferation and pro‐autophagy effects on hypoxic NP cells. However, these beneficial impact of H2 S on hypoxic NP cells were reversed by autophagy inhibitor. Conclusions: Our results showed that H2 S played a cytoprotective role in NP cells exposed to hypoxia in an autophagy‐dependent manner. Abstract : Hypoxia markedly impaired NP cell proliferation compared with control. Whereas H2 S donor provided pro‐proliferation and pro‐autophagy effects on hypoxic NP cells. However, these beneficial impact of H2 S to hypoxia were canceled out by autophagy inhibitor.